ANALISIS PERAN DAN KUALITAS SUMBER DAYA MANUSIA PERANGKAT DESA TERHADAP KINERJA DALAM PEMBEBASAN LAHAN HUTAN KONVERSI MENJADI HAK MILIK MASYARAKAT DI DESA TINGGIRAN DARAT KECAMATAN MEKARSARI KABUPATEN BARITO KUALA KALIMANTAN SELATAN - HUMAIDI HUMAIDI (JURNAL KINDAI, 2022)
The influence of the Role and Quality of Village Human Resources on Performance in the Acquisition of Converted Forest Land into the Property of the Tinggiran Darat Village Community, Mekarsari District, Barito Kuala Regency, South Kalimantan. This study aims to determine and analyze the influence of the role and quality of human resources of village officials simultaneously on performance in the acquisition of conversion forest land into the property of the people of Tinggiran Darat Village, Mekarsari District, Barito Kuala Regency, South Kalimanta .Sources of primary data in this study is data obtained directly from respondents through a list of questions addressed to each respondent. And the respondents in this study were village officials. The method of analysis in this study is to use Multiple Linear analysis using the SPSS program. Prior to the path analysis process, the research instrument (questionnaire) was tested with validity and reliability tests as well as classical assumptions. The results all meet the criteria to be continued at the multiple linear analysis stage The Role of Village Apparatus and Quality of Human Resources Village Apparatus have a significant simultaneous effect on the Performance of Tinggiran Darat Village, Tinggiran Darat District, Barito Kuala Regency, South Kalimantan Province, Barito Kuala Regency. The correlation value shows a high level of relationship. The role of village officials has a positive and significant impact on performance in the acquisition of conversion forest land into the property of the people of Tinggiran Darat Village, Mekarsari District, Barito Kuala Regency, South Kalimantan. So that the higher the role of the village apparatus, the performance in the acquisition of conversion forest land into the property of the people of Tinggiran Darat Village, Mekarsari District, Barito Kuala Regency, South Kalimantan, will be better. Keywords: the role of village officials, Quality of Human Resources and Performance